Why invisible boundaries matter: imagined institutions and power. (1st December 2017) - Ray, Tim
Abstract : This paper develops an alternative to Erin Meyer's influential argument that national culture determines how people in a nation behave, thereby creating invisible boundaries that divide nations according to behavioural stereotypes. Whereas Meyer makes the implicit assumption that we could observe national culture and its effect on behaviour as if from a God's Eye point of view, we might do better to begin with an Insider's Eye perspective on whom we could trust to do what. If we take too much for granted, we may miss invisible boundaries that matter; which might have happened when the English executive, Michael Woodford, became president and CEO of Japan's Olympus Corporation, only to find himself fearing for his life after exposing fraud that his Japanese colleagues thought wise to hide. Woodford's startling story is used here to consider three conceptual questions. First, how might power mediated by what people imagine influence the evolution of institutional ecologies, together with invisible boundaries that divide insiders from outsiders? Second, why should management theorists move from an objective God's Eye perspective to Insider's Eye reflections on power mediated by imagined institutions? And third, if we want to avoid falling foul of invisible boundaries, what should we do?